Retrospective host-specificity testing shows Trissolcus basalis (Wollaston) and the native Trissolcus oenone (Dodd) (Hymenoptera: Scelionidae) have overlapping physiological host ranges in New Zealand - Saunders, Thomas E.; Avila, Gonzalo A.; Holwell, Gregory I. (Biological control, 2022)
•We tested the physiological host ranges of an introduced biocontrol agent (T. basalis) and native parasitoid (T. oenone).•T. basalis attacks and develops in all nine pentatomid taxa we tested.•The native T. oenone attacks and develops in seven out of eight pentatomid species we tested.•Parasitism efficiencies were high for all treatments (>60%). Retrospective host range testing is essential for understanding the physiological host range of introduced biological control agents (BCAs) and updating forecasts of non-target risks. It is especially important to conduct this work if there was no host range testing prior to release of the agent. Trissolcus basalis Wollaston was released in New Zealand in 1949 against green vegetable bug (Nezara viridula [L.]), but host range testing was never undertaken, and subsequent work in the 1960s was only of a qualitative nature and remains incomplete. The host-parasitoid complex between New Zealand pentatomids, T. basalis, and the native pentatomid parasitoid Trissolcus oenone Dodd, is therefore poorly understood. We conducted no-choice oviposition tests between the two resident Trissolcus species and all available New Zealand pentatomid species to characterise the physiological (=fundamental) host ranges of these parasitoids. We present the results of the first retrospective host-specificity study on T. basalis in New Zealand. Our results show T. basalis attacks and develops in all nine pentatomid taxa we exposed it to (including the endemic alpine species Hypsithocus hudsonae Bergroth), while T. oenone attacks and develops in seven out of eight pentatomid species we tested it against (and its capacity to attack H. hudsonae remains unknown). Parasitism efficiencies for all treatments exceeded 60%, while development times were similar for both parasitoids regardless of host. We discuss the importance of physiological host range testing for understanding potential non-target effects. Trissolcus japonicus Ashmead (Hymenoptera: Scelionidae) was recently approved for release in New Zealand against brown marmorated stink bug Halyomorpha halys Stål (Hemiptera: Pentatomidae), subject to its potential establishment, and we examine our results in the context of potential competition between introduced parasitoids for non-target species.